2021
DOI: 10.1002/acs.3300
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis and fault‐tolerant control of uncertain network control systems

Abstract: Summary In this article, the equivalent control strategy based on Laplace transform is proposed for the problem of stochastic delay in networked control systems. The original system is transformed into an equivalent control system without random delay block by Laplace transform. Then, a new augmented variable and equivalent control system is introduced to construct an augmented system. An adaptive fault diagnosis observer is designed based on the augmented system. The adaptive turning rate of the observer is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Thus, the nonlinear characteristics can not be overlooked in fault estimation. At present, more and more attention is paid to the research of nonlinear systems for fault estimation and considerable research results have been reported on this topic, such as References 24‐30. In practice, lipschitz nonlinear systems in nonlinear control system models are broadly applied in practical problems, such as robots or aircraft control systems with trigonometric nonlinear terms in References 5,6,14,31,32.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the nonlinear characteristics can not be overlooked in fault estimation. At present, more and more attention is paid to the research of nonlinear systems for fault estimation and considerable research results have been reported on this topic, such as References 24‐30. In practice, lipschitz nonlinear systems in nonlinear control system models are broadly applied in practical problems, such as robots or aircraft control systems with trigonometric nonlinear terms in References 5,6,14,31,32.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of science and technology, the complexity of modern control system is increasing which often leads to the failures of control systems. To reduce the impact caused by system faults and improve the reliability of control systems, fault-tolerant control (FTC) problems [1][2][3][4][5][6][7] have been extensively investigated during the past decades. In general, FTC strategies can be categorized into two groups: passive control strategy [8][9][10] and active control strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Networked control systems (NCSs) have been widely developed in many fields, such as information processing and signal detection 1‐5 . In the past decades, there has been an increasing interest in NCSs due to the benefits of low cost and high reliability, and researchers have made numerous achievements 6‐10 .…”
Section: Introductionmentioning
confidence: 99%
“…Networked control systems (NCSs) have been widely developed in many fields, such as information processing and signal detection. [1][2][3][4][5] In the past decades, there has been an increasing interest in NCSs due to the benefits of low cost and high reliability, and researchers have made numerous achievements. [6][7][8][9][10] Since NCSs are vulnerable to undesirable factors such as disturbances, faults and attacks, the research on filter design for NCSs has attracted considerable attention in recent years.…”
Section: Introductionmentioning
confidence: 99%